PmVRP15, a Novel Viral Responsive Protein from the Black Tiger Shrimp, Penaeus monodon, Promoted White Spot Syndrome Virus Replication - Tipachai Vatanavicharn; Adisak Prapavorarat; Phattarunda Jaree; Kunlaya Somboonwiwat; Anchalee Tassanakajon (My University, 2014)
Suppression subtractive hybridization of Penaeus monodon hemocytes challenged with white spot syndrome virus (WSSV) has identified the viral responsive gene, PmVRP15, as the highest up-regulated gene ever reported in shrimps. Expression analysis by quantitative real time RT-PCR revealed 9410–fold up-regulated level at 48 h post WSSV injection. Tissue distribution analysis showed that PmVRP15 transcript was mainly expressed in the hemocytes of shrimp. The full-length cDNA of PmVRP15 transcript was obtained and showed no significant similarity to any known gene in the GenBank database. The predicted open reading frame of PmVRP15 encodes for a deduced 137 amino acid protein containing a putative transmembrane helix. Immunofluorescent localization of the PmVRP15 protein revealed it accumulated around the nuclear membrane in all three types of shrimp hemocytes and that the protein was highly up-regulated in WSSV-infected shrimps. Double-stranded RNA interference-mediated gene silencing of PmVRP15 in P. monodon significantly decreased WSSV propagation compared to the control shrimps (injected with GFP dsRNA). The significant decrease in cumulative mortality rate of WSSV-infected shrimp following PmVRP15 knockdown was observed. These results suggest that PmVRP15 is likely to be a nuclear membrane protein and that it acts as a part of WSSV propagation pathway.
Keywords: White spot syndrome; Penaeus monodon; Suppression subtractive hybridization; RNA Silencing; Invertebrate Immune Response Mechanisms